Assembly of noncentrosymmetric coordination polymers by the integration of acentric Ba(ii)/Sr(ii) and Li(i) coordination polyhedra1. Issue 18 (14th May 2015) - Song, Ying; Lin, Chen-Sheng; Zhang, Ming-Jian; Wei, Qi; Feng, Mei-Ling; Huang, Xiao-Ying
<x xml:space="preserve">Abstract</x> Presented is a strategy to construct noncentrosymmetric CPs through the integration of acentric [LiOxN4−x] and [BaOxNy] coordination polyhedra via bridging organic ligands.